Health equity and COVID-19: global perspectives - Efrat Shadmi; Yingyao Chen; Inês Dourado; Inbal Faran-Perach; John Furler; Peter Hangoma; Piya Hanvoravongchai; Claudia Obando; Varduhi Petrosyan; Krishna D. Rao; Ana Lorena Ruano; Leiyu Shi; et al. (BMC, 2020)
Abstract The COVID-19 is disproportionally affecting the poor, minorities and a broad range of vulnerable populations, due to its inequitable spread in areas of dense population and limited mitigation capacity due to high prevalence of chronic conditions or poor access to high quality public health and medical care. Moreover, the collateral effects of the pandemic due to the global economic downturn, and social isolation and movement restriction measures, are unequally affecting those in the lowest power strata of societies. To address the challenges to health equity and describe some of the approaches taken by governments and local organizations, we have compiled 13 country case studies from various regions around the world: China, Brazil, Thailand, Sub Saharan Africa, Nicaragua, Armenia, India, Guatemala, United States of America (USA), Israel, Australia, Colombia, and Belgium. This compilation is by no-means representative or all inclusive, and we encourage researchers to continue advancing global knowledge on COVID-19 health equity related issues, through rigorous research and generation of a strong evidence base of new empirical studies in this field.